Intelligence quotient discrepancy indicates levels of motor competence in preschool children at risk for developmental delays - Yu T; Chen K; Chou W; Yang S; Kung S; Lee Y; Tung L (Neuropsychiatric Disease and Treatment, 2016)
Tzu-Ying Yu,1 Kuan-Lin Chen,2,3 Willy Chou,4,5 Shu-Han Yang,4 Sheng-Chun Kung,4 Ya-Chen Lee,2 Li-Chen Tung4,6,7 1Department of Occupational Therapy, College of Medicine, I-Shou University, Kaohsiung, 2Department of Occupational Therapy, College of Medicine, National Cheng Kung University, Tainan, 3Department of Physical Medicine and Rehabilitation, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, 4Department of Physical Medicine and Rehabilitation, Chi-Mei Medical Center, Tainan, 5Department of Recreation and Health Care Management, Cha Nan University of Pharmacy and Science, Tainan, 6School of Medicine, Kaohsiung Medical University, Kaohsiung, 7School of Medicine, Chung Shan Medical University, Taichung, Taiwan Purpose: This study aimed to establish 1) whether a group difference exists in the motor competence of preschool children at risk for developmental delays with intelligence quotient discrepancy (IQD; refers to difference between verbal intelligence quotient [VIQ] and performance intelligence quotient [PIQ]) and 2) whether an association exists between IQD and motor competence.Methods: Children’s motor competence and IQD were determined with the motor subtests of the Comprehensive Developmental Inventory for Infants and Toddlers and Wechsler Preschool and Primary Scale of Intelligence™ – Fourth Edition. A total of 291 children were included in three groups: NON-IQD (n=213; IQD within 1 standard deviation [SD]), VIQ>PIQ (n=39; VIQ>PIQ greater than 1 SD), and PIQ>VIQ (n=39; PIQ>VIQ greater than 1 SD).Results: The results of one-way analysis of variance indicated significant differences among the subgroups for the “Gross and fine motor” subdomains of the Comprehensive Developmental Inventory for Infants and Toddlers, especially on the subtests of “body-movement coordination” (F=3.87, P<0.05) and “visual-motor coordination” (F=6.90, P<0.05). Motor competence was significantly worse in the VIQ>PIQ group than in the NON and PIQ>VIQ groups. Significant negative correlations between IQD and most of the motor subtests (r=0.31–0.46, P<0.01) were found only in the VIQ>PIQ group.Conclusion: This study demonstrates that 1) IQD indicates the level of motor competence in preschoolers at risk for developmental delays and 2) IQD is negatively associated with motor competence in preschoolers with significant VIQ>PIQ discrepancy. The first finding was that preschoolers with VIQ>PIQ discrepancy greater than 1 SD performed significantly worse on motor competence than did preschoolers without significant IQD and preschoolers with PIQ>VIQ discrepancy greater than 1 SD. However, preschoolers with significant PIQ>VIQ discrepancy performed better on motor competence than did preschoolers without significant IQD, though the difference was not statistically significant. The second finding was that preschoolers with larger VIQ>PIQ discrepancy had worse motor competence in visual-motor integration and body-movement coordination. Professionals should pay attention to the motor development of children with VIQ>PIQ discrepancy and evaluate children’s IQD along with their motor competence. Keywords: IQ discrepancy, motor competence, child